Why partitive? Possible motivations for the partitive complement of Finnic adpositions - Huumo, Tuomas (Estonia, 2025)
Adpositions localize an entity (Figure) with respect to another entity (Ground), designated by the complement of the adposition. Most Finnic adpositions are postpositions with a genitive Ground, while prepositions typically have a partitive Ground. This work is a cognitive-linguistic study of the synchronic and diachronic semantics of partitive-Ground adpositions. It is argued that adpositions with a partitive Ground select a proximal perspective to the locational relationship, while those with a genitive Ground select a distal perspective. Three alternative hypotheses are introduced and compared concerning the origin of two Finnish partitive-Ground adpositions, kohti ‘towards’ and päin ‘towards’: 1) These adpositions originated as instructive-case body-part expressions of position (cf. selin ‘with one’s back at’), and their partitive Ground
indicated a viewpoint person; 2) They were instructive forms with a meronymic-locative meaning, expressing a more precise target area within the Ground, together with a directionality toward that area; 3) The Ground of kohti and päin was originally a partitive object of ‘aiming’ or ‘shooting’ verbs, and the soon-to-be adpositions themselves were lexicalized adverbs of direction.